Splenic metastasis from endometrial adenocarcinoma. A case presentation - Jorge Felipe Montero León; Tania Rosa Escalona Ramírez; Solangel Álvarez Sánchez (Universidad de Ciencias Médicas de La Habana, 2020)
Introduction: Splenic metastasis from endometrial carcinoma is a rare clinical event with only 13 documented cases in the literature reviewed. The evolution of a patient with this metastasis attended in our institution was the reason that motivated us to publish this work. There are other oncological diseases that are accompanied by this clinical picture during their evolution of progression where surgical treatment complemented with chemotherapy treatment is essential. A literature review was carried out in Cuban publications, but no reports on the topic were found. Objective: The aim of this work is to present an endometroid type case endometrium adenocarcinoma which metastasizes to the spleen with clear cell histology. Case presentation:  Forty-five-year-old patient with diagnosis of endometrium adenocarcinoma with surgical stage pT3a Nx Mo stage IIIA Grade 2; this quantification was defined before 2009.  The patient underwent surgical treatment which was complemented with radiotherapy and then followed for 21 months.  In the follow-up consultation, spleen metastasis was diagnosed; so she underwent splenectomy and was treated with chemotherapy.  She was treated by the multidisciplinary gynecologic oncology team; the investigations performed were based on immuhistochemistry, imaging, and supportive treatment whenever needed. Conclusions:  Splenic metastasis from endometrial cancer is rare; it is the first case reported in Cuba.  Immuhistochemical and imaging studies are essential.